Simpulan bahasa Bidayuh Bukar Sadong: Analisis Semantik Kognitif - Zizianie Elvy, Apan (Universiti Malaysia Sarawak (UNIMAS), 2022)
This study aims to examine the Bidayuh Bukar Sadong (BBS) idioms related to the behavior of the Bidayuh community around Serian, Sarawak. The objective of this study is to explain the meaning of idioms as well as describe the idioms of the Bidayuh community related to aspects of behavior based on cognitive semantic approach by using the image schema mechanism pioneered by Lakoff (1987). A total of 16 informants, namely 8 males and 8 females were interviewed semi -structured to obtain information on BBS idioms. All informants are Bidayuh individuals aged 40 years and above who live in Kampung Koran Mawang, Serian and speak the BBS language. The data obtained were analyzed using the image schema mechanism pioneered by Lakoff (1987). The results showed that the 20 data for the BBS idiom fit the theme of the study, namely behavior. The analyzed data applied 5 types of image schemas highlighted by Lakoff (1987), namely Top-Bottom image scheme, Size image scheme, Container image scheme, Part-Whole image scheme, and Source-Path-Goal image scheme. Through this study, the wisdom of thinking of the Bidayuh community, Serian in the creation of BBS idioms can be explained systematically through the application of cognitive semantic framework in addition to adding knowledge for all communities, especially the younger generation.